1921
DOI: 10.1007/bf02593644
|View full text |Cite
|
Sign up to set email alerts
|

Morphologie und Morphogenese des Haarstrichs

Abstract: Einleitung. g u g e a L u d w i g : Gebieten aus, bedecken Flfi.ehen yon weehselnder Ausdehnung und enden an Linien oder in Punkten. Sie kSnnen im Verlaufe eines Stromes bald divergieren, bald konvergieren, bald parallel eingestellt sein. je naehdem die Breite des Strorues. wgchst, abnimmt oder sieh gleichbteibt. Was man unter konver~erenden und divergierenden Wirbeln und Linien und was unter Kreuzen sieh vorzustellen hat, darf wohl, wie die Kenntnis'der Arbeiten yon E s e h r i c h t (1837), V o i g t (1857) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1943
1943
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…14,16 In 1921 Ludwig also indicated that lanugo patterns become "clear and explicit" in the 5 th month of fetal life. 7 The present study shows that the first single hairs appear on the posterior wall of the trunk in the 17 th gestational week, and on the anterior wall between the 18 th and 19 th gestational weeks. Plikus and Chuong suggested that the first developmental hair cycle in a mammal's life starts in the cephalic part of the mammal, then "wanders" distally, first to the back, then the abdomen and finally reaching the limbs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…14,16 In 1921 Ludwig also indicated that lanugo patterns become "clear and explicit" in the 5 th month of fetal life. 7 The present study shows that the first single hairs appear on the posterior wall of the trunk in the 17 th gestational week, and on the anterior wall between the 18 th and 19 th gestational weeks. Plikus and Chuong suggested that the first developmental hair cycle in a mammal's life starts in the cephalic part of the mammal, then "wanders" distally, first to the back, then the abdomen and finally reaching the limbs.…”
Section: Discussionsupporting
confidence: 56%
“…Ludwig only states that lanugo patterns are "clear and explicit" in fetuses at the 5 th -6 th month of gestation. 7 According to Muller et al, fetal hair begin to develop at the early embryological stages, presumably between the 9 th and 12 th week of pregnancy. 8 Irmak et al noticed that when the adrenal cortex starts to produce dehydroepiandrosterone sulfate (DHEA-S) at the early stage of pregnancy (8 th -10 th week), the initiation of hair and sebaceous gland differentiation follows.…”
mentioning
confidence: 99%